The empowerment of women and youth in Ethiopia through small ruminants and access to agro-advisory services - Gondwe, Therese; Huyer, Sophia; Tesfaye, Abonesh; Radeny, Maren; Tesfaye , Brook (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
AICCRA Ethiopia works through partnerships to scale the knowledge, innovation and technologies needed for effective climate information services and climate-smart agriculture in Ethiopia. This is done by working with smallholder farmers and livestock keepers. Such innovations include Women-led Community Based Breeding Program and promoting accesss to climate advisory services by small holder farmers. This has resulted in empowering women through their involvement in decision making processes.